1
$\begingroup$

Having a bit of trouble here.

Having this integral $$ \int_{0}^{\infty} \frac{dx}{(x^{2}+1)(x^{2}+4)^{2}} $$ I can tell it's even, so it has symmetry. Thus, $$ \frac{1}{2} \int_{-\infty}^{\infty} \frac{dx}{(x^{2}+1)(x^{2}+4)^{2}} $$ The function $f(z)$ has poles at $ \pm i $ and $ \pm 2i $, but i can only focus on $i$ and $2i$ since I will use the residue theorem with a semicircular contour in the upper half plane.

Now this is the part that confuses me, $$ Res_{z=i}f(z) = \frac{d}{dz} \frac{1}{(z+i)(z+2i)^2(z-2i)^2} $$

When trying to solve for it, I get a completely different answer than mathematica gives. What is the most optimal and practical way of evaluating this?

$\endgroup$
4
  • $\begingroup$ At $i$, the integrand has a simple pole, so you shouldn't differentiate, the residue at $i$ is simply $\frac{1}{(i+i)(i^2+4)^2} = \frac{1}{18i}$. $\endgroup$ Mar 6, 2016 at 16:53
  • $\begingroup$ Do you 'have to' use residues? $\endgroup$ Mar 6, 2016 at 17:12
  • $\begingroup$ @DanielFischer okay, thats what i thought. But would i only differentiate when looking for the pole of order 2? $\endgroup$
    – iron2man
    Mar 6, 2016 at 18:51
  • $\begingroup$ Yes, you'd only differentiate for poles of order $> 1$. It is however often more convenient to use other techniques. Here a partial fraction decomposition is an option, and for small orders of the pole, a Taylor expansion of the holomorphic factor to the required order is often less work than differentiating. $\endgroup$ Mar 6, 2016 at 19:06

1 Answer 1

0
$\begingroup$

$$\int_{0}^{\infty}\frac{1}{\left(x^2+1\right)\left(x^2+4\right)^2}\space\text{d}x=\lim_{n\to\infty}\int_{0}^{n}\frac{1}{\left(x^2+1\right)\left(x^2+4\right)^2}\space\text{d}x=$$ $$\lim_{n\to\infty}\int_{0}^{n}\left[\frac{1}{9\left(x^2+1\right)}-\frac{1}{3\left(x^2+4\right)^2}-\frac{1}{9\left(x^2+4\right)}\right]\space\text{d}x=$$ $$\lim_{n\to\infty}\left[\int_{0}^{n}\frac{1}{9\left(x^2+1\right)}\space\text{d}x-\int_{0}^{n}\frac{1}{3\left(x^2+4\right)^2}\space\text{d}x-\int_{0}^{n}\frac{1}{9\left(x^2+4\right)}\space\text{d}x\right]=$$ $$\lim_{n\to\infty}\left[\frac{1}{9}\int_{0}^{n}\frac{1}{x^2+1}\space\text{d}x-\frac{1}{3}\int_{0}^{n}\frac{1}{\left(x^2+4\right)^2}\space\text{d}x-\frac{1}{9}\int_{0}^{n}\frac{1}{x^2+4}\space\text{d}x\right]=$$ $$\lim_{n\to\infty}\left[\frac{1}{9}\int_{0}^{n}\frac{1}{x^2+1}\space\text{d}x-\frac{1}{3}\int_{0}^{n}\frac{1}{\left(x^2+4\right)^2}\space\text{d}x-\frac{1}{9}\int_{0}^{n}\frac{1}{4\left(\frac{x^2}{4}+1\right)}\space\text{d}x\right]=$$ $$\lim_{n\to\infty}\left[\frac{1}{9}\int_{0}^{n}\frac{1}{x^2+1}\space\text{d}x-\frac{1}{3}\int_{0}^{n}\frac{1}{\left(x^2+4\right)^2}\space\text{d}x-\frac{1}{36}\int_{0}^{n}\frac{1}{\frac{x^2}{4}+1}\space\text{d}x\right]=$$


For the integrand $\frac{1}{\frac{x^2}{4}+1}$, substitute $u=\frac{x}{2}$ and $\text{d}u=\frac{1}{2}\space\text{d}x$.

This gives a new lower bound $u=\frac{0}{2}=0$ and upper bound $u=\frac{n}{2}$:


$$\lim_{n\to\infty}\left[\frac{1}{9}\int_{0}^{n}\frac{1}{x^2+1}\space\text{d}x-\frac{1}{3}\int_{0}^{n}\frac{1}{\left(x^2+4\right)^2}\space\text{d}x-\frac{1}{18}\int_{0}^{\frac{n}{2}}\frac{1}{u^2+1}\space\text{d}u\right]=$$ $$\lim_{n\to\infty}\left[\frac{1}{9}\left[\arctan(x)\right]_{0}^{n}-\frac{1}{3}\int_{0}^{n}\frac{1}{\left(x^2+4\right)^2}\space\text{d}x-\frac{1}{18}\left[\arctan(u)\right]_{0}^{\frac{n}{2}}\right]=$$ $$\lim_{n\to\infty}\left[\frac{\arctan(n)-\arctan(0)}{9}-\frac{1}{3}\int_{0}^{n}\frac{1}{\left(x^2+4\right)^2}\space\text{d}x-\frac{\arctan\left(\frac{n}{2}\right)-\arctan(0)}{18}\right]=$$ $$\lim_{n\to\infty}\left[\frac{\arctan(n)-0}{9}-\frac{1}{3}\int_{0}^{n}\frac{1}{\left(x^2+4\right)^2}\space\text{d}x-\frac{\arctan\left(\frac{n}{2}\right)-0}{18}\right]=$$ $$\lim_{n\to\infty}\left[\frac{\arctan(n)}{9}-\frac{1}{3}\int_{0}^{n}\frac{1}{\left(x^2+4\right)^2}\space\text{d}x-\frac{\arctan\left(\frac{n}{2}\right)}{18}\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{3}\int_{0}^{n}\frac{1}{\left(x^2+4\right)^2}\space\text{d}x\right]=$$


Substitute $x=2\tan(s)$ and $\text{d}x=2\sec^2(s)\space\text{d}s$.

Then $\left(x^2+4\right)^2=\left(4\tan^2(s)+4\right)^2=16\sec^4(s)$ and $s=\arctan\left(\frac{x}{2}\right)$.

This gives a new lower bound $s=\arctan\left(\frac{0}{2}\right)=0$ and upper bound $s=\arctan\left(\frac{n}{2}\right)$:


$$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{2}{3}\int_{0}^{\arctan\left(\frac{n}{2}\right)}\frac{\cos^2(s)}{16}\space\text{d}s\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{24}\int_{0}^{\arctan\left(\frac{n}{2}\right)}\cos^2(s)\space\text{d}s\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{24}\int_{0}^{\arctan\left(\frac{n}{2}\right)}\left[\frac{1}{2}+\frac{\cos(2s)}{2}\right]\space\text{d}s\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{24}\left[\frac{1}{2}\int_{0}^{\arctan\left(\frac{n}{2}\right)}1\space\text{d}s+\frac{1}{2}\int_{0}^{\arctan\left(\frac{n}{2}\right)}\cos(2s)\space\text{d}s\right]\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{24}\left[\frac{1}{2}\left[x\right]_{0}^{\arctan\left(\frac{n}{2}\right)}+\frac{1}{2}\int_{0}^{\arctan\left(\frac{n}{2}\right)}\cos(2s)\space\text{d}s\right]\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{24}\left[\frac{\arctan\left(\frac{n}{2}\right)-0}{2}+\frac{1}{2}\int_{0}^{\arctan\left(\frac{n}{2}\right)}\cos(2s)\space\text{d}s\right]\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{24}\left[\frac{\arctan\left(\frac{n}{2}\right)}{2}+\frac{1}{2}\int_{0}^{\arctan\left(\frac{n}{2}\right)}\cos(2s)\space\text{d}s\right]\right]=$$


Substitute $p=2s$ and $\text{d}p=2\space\text{d}s$.

This gives a new lower bound $p=2\cdot0=0$ and upper bound $p=2\arctan\left(\frac{n}{2}\right)$:


$$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{24}\left[\frac{\arctan\left(\frac{n}{2}\right)}{2}+\frac{1}{4}\int_{0}^{2\arctan\left(\frac{n}{2}\right)}\cos(p)\space\text{d}p\right]\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{24}\left[\frac{\arctan\left(\frac{n}{2}\right)}{2}+\frac{1}{4}\left[\sin(p)\right]_{0}^{2\arctan\left(\frac{n}{2}\right)}\right]\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{24}\left[\frac{\arctan\left(\frac{n}{2}\right)}{2}+\frac{\sin\left(2\arctan\left(\frac{n}{2}\right)\right)-\sin(0)}{4}\right]\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{24}\left[\frac{\arctan\left(\frac{n}{2}\right)}{2}+\frac{\sin\left(2\arctan\left(\frac{n}{2}\right)\right)-0}{4}\right]\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{1}{24}\left[\frac{\arctan\left(\frac{n}{2}\right)}{2}+\frac{\sin\left(2\arctan\left(\frac{n}{2}\right)\right)}{4}\right]\right]=$$ $$\lim_{n\to\infty}\left[\frac{2\arctan(n)-\arctan\left(\frac{n}{2}\right)}{18}-\frac{2\arctan\left(\frac{n}{2}\right)+\sin\left(2\arctan\left(\frac{n}{2}\right)\right)}{96}\right]=$$ $$\lim_{n\to\infty}\left[\frac{32\arctan(n)-22\arctan\left(\frac{n}{2}\right)-3\sin\left(\arctan\left(\frac{n}{2}\right)\right)}{288}\right]=$$ $$\frac{1}{288}\lim_{n\to\infty}\left[32\arctan(n)-22\arctan\left(\frac{n}{2}\right)-3\sin\left(\arctan\left(\frac{n}{2}\right)\right)\right]=$$ $$\frac{1}{288}\left[32\lim_{n\to\infty}\arctan(n)-22\lim_{n\to\infty}\arctan\left(\frac{n}{2}\right)-3\lim_{n\to\infty}\sin\left(\arctan\left(\frac{n}{2}\right)\right)\right]=$$ $$\frac{1}{288}\left[32\cdot\frac{\pi}{2}-22\cdot\frac{\pi}{2}-3\cdot0\right]=$$ $$\frac{1}{288}\left[32\cdot\frac{\pi}{2}-22\cdot\frac{\pi}{2}-0\right]=$$ $$\frac{1}{288}\left[32\cdot\frac{\pi}{2}-22\cdot\frac{\pi}{2}\right]=$$ $$\frac{1}{288}\left[5\pi\right]=\frac{5\pi}{288}$$

So:

$$\color{red}{\int_{0}^{\infty}\frac{1}{\left(x^2+1\right)\left(x^2+4\right)^2}\space\text{d}x=\frac{5\pi}{288}}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.